Dreaming during the COVID-19 lockdown: a comparison of Italian adolescents and adults - Massimiliano Sommantico (Research in Psychotherapy, 2021)
Based on the continuity hypothesis of dreaming, we have studied the effects of lockdown measures on Italian adolescents’ and adults’ dreams during the first wave of the coronavirus disease 2019 (COVID-19) pandemic. A sample of 475 subjects (73.9% women; 48.4% adolescents; ages 12-70 years, M=25.10, SD=12.2) was recruited via the Internet between April 17, 2020 and May 18, 2020. Participants were asked to provide socio-demographic data, as well as to report their Most Recent Dream. Results indicated that adults’ dreams were the longest, as well as characterized by higher emotional intensity, predominantly negative emotions, and a higher presence of sensory impressions. Furthermore, results indicated that the participants, especially adolescents, who were most directly affected by the COVID-19 pandemic reported the strongest effects on their dreams. Results also indicated that women recall dreams more often than men, in addition to reporting higher emotional intensity, predominantly negative emotions, and a higher presence of sensory impressions. Finally, results of the Thematic Analysis of Elementary Contexts showed that adults’ dreams seem to be centered, above all, on both pleasant memories linked to experiences that are now forbidden (i.e., traveling, meeting friends) as well as on nightmares, while adolescents’ dreams focused on relationships with others. Finally, both adults and adolescents reported dreams related to the experience of home confinement, which they described in terms of the negative emotions they experienced. In sum, the findings of this study indicate that the COVID-19 lockdown measures, understood as a contextual and traumatic event, significantly affect people’s oneiric lives, regardless of age.